1997
DOI: 10.1046/j.1365-2141.1997.2733092.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow innervation regulates cellular retention in the murine haemopoietic system

Abstract: Summary. An anatomical analysis of the innervation of murine femora revealed intimate association of haemopoietic and stromal cells with nerve fibres. The mechanical denervation of these femora resulted in significant mobilization of cells into the peripheral blood within 24 h. There was a decrease in femoral cellularity and analysis of the type of cells mobilized also revealed that there was an increase in progenitor cells in the peripheral blood. In non-splenectomized mice these progenitor cells were quickly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 23 publications
2
77
2
1
Order By: Relevance
“…Within 24 h after transecting the femoral nerve, or after chemical sympathectomy with 6-OHDA, bone marrow cellularity decreases [9]. This effect is due to the egress of mature and progenitor hematopoetic cells into the peripheral blood [9]. In another study, NE mobilized fat from the bone marrow [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within 24 h after transecting the femoral nerve, or after chemical sympathectomy with 6-OHDA, bone marrow cellularity decreases [9]. This effect is due to the egress of mature and progenitor hematopoetic cells into the peripheral blood [9]. In another study, NE mobilized fat from the bone marrow [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, noradrenergic (NA) influences on immunity, while still not entirely understood, have been the most extensively investigated. Neural regulation of immune function by peptide neurotransmitters that co-localize with NE, such as neuropeptide Y (NPY), adenosine triphosphate (ATP), opioid peptides, corticotropin-releasing hormone (CRH) and vasoactive NA nerves closely associate with hematopoietic and stromal cells in the bone marrow [2,[4][5][6][7][8][9]. Sympathetic nerve terminals directly appose periarterial adventitial cells, a particular type of stromal cell, that is an important source of growth factors and adhesion molecules [8].…”
Section: Introductionmentioning
confidence: 99%
“…The study also indicates a possible nervous control of cell proliferation within the bone marrow [4].…”
mentioning
confidence: 86%
“…It has been suggested that nerve fibers contribute to the regulation of blood cell production, although there is some controversy about these findings. [41][42][43][44] Based on these findings taken together, it can be speculated that the growth-promoting effect of VIP on hematopoietic progenitor cells is exerted predominantly in the vicinity of VIP-producing nerve terminals in the BM microenvironment. How the growth-promoting effects of VIP contribute to the in vivo regulation of hematopoiesis remains unknown and should be investigated in future studies.…”
Section: Cd34mentioning
confidence: 99%